Perencanaan Enterprise Arsitektur Menggunakan Framework Togaf pada Aplikasi Srikandi : Studi Kasus : Kantor Kecamatan Baturraden - Vellyn Chalista Elfanza; Vita Dwi Utami; Rindiana Putri Natasya; Rahayu Linda Kusuma; Ito Setiawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Information technology (IT) has developed rapidly and is known to be the most important part of all aspects of life, such as education, business, and also government. Information technology allows organizations to increase efficiency and create innovative solutions and has an important role in improving the accountability of public services, especially in the aspect of government. The development of technology in the government aspect has an important role. One of the innovations in Indonesia is the SRIKANDI (Integrated Dynamic Archives Information System) application. SRIKANDI is an application developed to digitize archive and document management in government. The development of enterprise architecture in government institutions is crucial in ensuring that information systems can support processes effectively and efficiently. This research aims to develop enterprise architecture using the TOGAF (The Open Group Architecture Framework) method on the SRIKANDI application at the Baturraden District Office. The SRIKANDI application, which is an Integrated Dynamic Archive Information System, plays an important role in digitizing government archive management. The TOGAF method was chosen for its comprehensive approach in designing, implementing, and managing information system architecture.